Reliability and validity of outcome measures used for urinary incontinence in patients with stroke: a narrative review. (17th December 2020) - Doyle, Emma; Brettkelly, Jake; Buhler, Rebecca; Lovett, Tim; O'Neil, Luke; Aldabe, Daniela
Abstract: Background: Worldwide the prevalence of stroke is increasing and is a major cause of disability in adults, leading to difficulty with activities of daily living and decreased quality of life. Urinary incontinence (UI) is a common symptom post-stroke with up to 79% of patients reporting it within the first month after the brain injury. Objectives: The aim of this review is to investigate the suitability of UI outcome measures via psychometric analysis in post-stroke populations. The study involved reviewing the literature outlined in a recent Cochrane Review and identifying the reliability and validity of the selected outcome measures. Major findings: Out of 13 outcome measures, two had their reliability, and three had their validity assessed in a population that included patients with stroke. Conclusion: Selecting appropriate outcome measures in research contributes to internal validity of a study. Hence, further studies assessing the reliability and validity of UI outcome measures including patients with stroke is necessary. Ideally, evaluating clinical progression of a patient should be conducted using population-specific outcomes measures.